2009
DOI: 10.1136/hrt.2008.161174
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative 6-minute walk test adds prognostic information to Euroscore in patients undergoing aortic valve replacement

Abstract: The 6MWT is safe and feasible to carry out in patients with severe aortic stenosis before AVR, and provides potentially important functional and prognostic information to clinical assessment and the Euroscore risk score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 19 publications
0
50
0
4
Order By: Relevance
“…The European System for Cardiac Operation Risk Evaluation II has been shown to overestimate mortality in isolated patients undergoing CABG,40 whereas the Society of Thoracic Surgeons score underestimates it 13. However, the incorporation of a frailty score into such risk models has been shown to improve model discrimination 14, 23, 24. The high burden of frailty in patients undergoing CABG accentuates the need for further research to validate these more inclusive risk scores in larger population‐based cohorts and for prospective trials guided by these new scores to determine whether alternative revascularization strategies (eg, percutaneous coronary intervention) and/or comprehensive preoperative nutritional, psychological support, and physical conditioning programs would improve outcomes in frail patients 41, 42, 43…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The European System for Cardiac Operation Risk Evaluation II has been shown to overestimate mortality in isolated patients undergoing CABG,40 whereas the Society of Thoracic Surgeons score underestimates it 13. However, the incorporation of a frailty score into such risk models has been shown to improve model discrimination 14, 23, 24. The high burden of frailty in patients undergoing CABG accentuates the need for further research to validate these more inclusive risk scores in larger population‐based cohorts and for prospective trials guided by these new scores to determine whether alternative revascularization strategies (eg, percutaneous coronary intervention) and/or comprehensive preoperative nutritional, psychological support, and physical conditioning programs would improve outcomes in frail patients 41, 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of frailty can be made with clinical scales,22 functional assessments,13, 23 and their combination,24 or by the presence of a constellation of frailty‐defining diagnoses 5, 8, 25. This last method uses the Johns Hopkins Adjusted Clinical Groups (ACG) frailty‐defining diagnoses indicator, which is an instrument based on 10 clusters of frailty‐defining diagnoses (ie, malnutrition, dementia, impaired vision, decubitus ulcer, incontinence of urine, loss of weight, poverty, barriers to access to care, difficulty in walking, and falls; Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…de Arenaza et al (39) found the 6-minute walking test (defining frailty as a walking distance of under 300 m) to be an independent predictor of mortality, infarction and major cardiac and cerebrovascular adverse events one year after surgery. Another finding of this study was that the 6-minute walking test applied to patients at increased risk according to the EuroSCORE I (mortality rate >6%) was able to improve the stratification of surgical risk into low and high risk profiles, improving its predictive and discriminating capacity.…”
Section: Importance Of Patient Frailty In Emergent Surgery Of the Aormentioning
confidence: 99%
“…These instruments range from simple scores such as the gait speed (5-meter walk) test or the 6-minute walking test, which only assess the presence or absence of "physical frailty" (38,39), to the very comprehensive 70-item Frailty Index, which moreover explores cognitive, sociocultural and familial aspects and global patient disability (40).…”
Section: Importance Of Patient Frailty In Emergent Surgery Of the Aormentioning
confidence: 99%
“…Preoperative six minute walk test with a cutoff value of 300 meters was utilized in patients undergoing AVR in a recent trial (de Arenaza et al, 2010). It was indicated that six minute walk test added prognostic information to EuroSCORE and was an independent predictor of the composite outcome of death, myocardial infarction or stroke at 12 months.…”
Section: Evaluation and Managementmentioning
confidence: 99%